Acute kidney injury defined by cystatin C may be superior for predicting the outcomes of liver cirrhosis with acute gastrointestinal bleeding. Issue 1 (31st December 2022) - Hong, Cen; Zhu, Qiang; Li, Yiling; Tang, Shanhong; Lin, Su; Yang, Yida; Yuan, Shanshan; Shao, Lichun; Wu, Yunhai; Liu, Bang; Li, Bimin; Meng, Fanping; et al.
Abstract: Background & Aims: Acute kidney injury (AKI) is conventionally evaluated by a dynamic change of serum creatinine (Scr). Cystatin C (CysC) seems to be a more accurate biomarker for assessing kidney function. This retrospective multicenter study aims to evaluate whether AKI re-defined by CysC can predict the in-hospital outcomes of patients with liver cirrhosis and acute gastrointestinal bleeding. Methods: Overall, 677 cirrhotic patients with acute gastrointestinal bleeding, in whom both Scr and CysC levels were detected at admissions, were screened. eGFRScr, eGFRCysC, and eGFRScr-CysC were calculated. MELD-Na score and AKI were re-evaluated by CysC instead of Scr. Odds ratios (ORs) were calculated in the logistic regression analyses. The receiver operating characteristic (ROC) curve analyses were performed. Results: Univariate logistic regression analyses demonstrated that baseline Scr and CysC levels, eGFRScr, eGFRCysC, eGFRScr-CysC, original MELD-Na score defined by Scr, MELD-Na score re-defined by CysC, and AKI re-defined by CysC, but not conventional AKI defined by Scr, were significantly associated with in-hospital death. ROC analyses showed that baseline CysC level, eGFRScr, eGFRCysC, eGFRScr-CysC, original MELD-Na score defined by Scr, and MELD-Na score re-defined by CysC, but not baseline Scr level, could significantly predict the risk of in-hospital death. Conclusions: AKI re-defined by CysC may be superior for predicting the in-hospital mortality of cirrhotic patients with acute gastrointestinal bleeding.